Experimental Study of the Combustion Process of Gaseous Fuels Containing Nitrogen Compounds in New, Low-emission Zonal Volumetric Combustion Technology. (August 2017) - Ślefarski, Rafał; Szewczyk, Dariusz; Jankowski, Radosław; Gołębiewski, Michał
Abstract: The paper presents the result of experimental investigations of the innovative Zonal Volumetric Combustion technology (ZVC) applying several methods for toxic compound reduction (NOX, CO and CX HY ) produced during the high combustion process of gaseous fuels in industrial combustion systems. In the ZVC technology, the volumetric combustion process of fuel takes place in two zones: the reducing zone and oxidizing zone. The experimental studies included the influence of fuel-bound nitrogenous compounds like (NH3, pyridine) on the overall emission of NOX as well as the influence of high hydrocarbons (benzene) on CO, CX HY and soot formation.